Rural Financial Governance: A Public Policy Evaluation Of Traditional Agricultural Land Pawning Practices From The Perspective Of Yusuf Qardhawi - Syahidah Rahmah (Universitas Cahaya Prima, 2026)
The traditional practice of rice paddy pawning remains a financing mechanism used by rural communities to meet economic needs and capital for agricultural businesses. While it provides quick and easy access to financing, this practice often places farmers at a disadvantage, as the pawn recipient receives economic benefits from land management and harvests during the pawn period. This situation indicates problems in rural financing governance, particularly regarding the protection of farmers' productive assets and weak regulations governing the practice of rice paddy pawning. This study aims to evaluate the practice of traditional rice paddy pawning from a public policy perspective, analyze its alignment with Yusuf Qardhawi's concept of rahn, and formulate a policy model that can strengthen farmer protection. This study used a qualitative approach with a case study design in Balang Pasui Village, Jeneponto Regency. Data were obtained through interviews, observation, documentation, and literature review, then analyzed descriptively and comparatively. The results indicate that the traditional rice paddy pawning practice is effective as an alternative financing source, but does not fully meet the principles of justice, property rights protection, and welfare as proposed by Yusuf Qardhawi. Based on the analysis, this study formulates a Community-Based Sharia Rahn Policy model that integrates regulations for farmer asset protection, strengthening Islamic microfinance institutions, community-based supervision, and Islamic financial literacy. This model is expected to support the realization of fairer, more inclusive, and sustainable rural financial governance